2017
DOI: 10.1017/s1041610217000473
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and progression of mild cognitive impairment among clinic and community populations: a systematic review and meta-analysis

Abstract: Age and gender were observed to be associated with MCI, in which age was considered as an impact factor for DR. The strong heterogeneity may result from variations in study design and baselines. Standardized MCI criteria were suggested to systematically evaluate MCI in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 74 publications
6
107
3
7
Order By: Relevance
“…For instance, Xia et al reported that HOTAIR can promote metastasis in renal cell carcinoma by upregulating the histone demethylase JMJD3 [30]. In addition, a meta-analysis highlighted that HOTAIR was overexpressed in cancer tissues and actively participated in cancer occurrence and development [31]. Consistent with these findings, our study also found that HOTAIR expression was significantly enhanced in ovarian cancer and that its depletion suppressed ovarian cancer cell aggressiveness; this result was also in agreement with recent evidence that highly expressed HOTAIR was connected with Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry …”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xia et al reported that HOTAIR can promote metastasis in renal cell carcinoma by upregulating the histone demethylase JMJD3 [30]. In addition, a meta-analysis highlighted that HOTAIR was overexpressed in cancer tissues and actively participated in cancer occurrence and development [31]. Consistent with these findings, our study also found that HOTAIR expression was significantly enhanced in ovarian cancer and that its depletion suppressed ovarian cancer cell aggressiveness; this result was also in agreement with recent evidence that highly expressed HOTAIR was connected with Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry …”
Section: Discussionmentioning
confidence: 99%
“…cell lung cancer by interacting with cell cycle-related genes independent of glycolysis [17]. Aside from this, Na et al conducted multivariate analysis that revealed ALDOA as an independent and significant prognostic factor in clear cell renal cell carcinoma [18,19].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…The characteristic pathological changes of AD (senile plaques and neurofibrillary tangles) are already present in MCI . The prevalence of MCI among the older people in China is 14.7–20.8%, and approximately one ‐third of people with MCI will progress into AD . In spite of the increasing number of people with AD and MCI among the older people in China, less than 20% of these people have ever sought medical attention and most of them still exist in the communities.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The prevalence of MCI among the older people in China is 14.7-20.8%, 10,11 and approximately one -third of people with MCI will progress into AD. 12 In spite of the increasing number of people with AD and MCI among the older people in China, less than 20% of these people have ever sought medical attention 13 and most of them still exist in the communities. Therefore, brief and sensitive questionnaires are required to screen in communities for timely interventions.…”
mentioning
confidence: 99%